Lessons in love: Countering student belief in romantic love myths. Issue 5 (22nd September 2022) - Standley, Jeff
Abstract: The Department for Education recently administered new Relationships and Sex Education (RSE) guidance, one of the aims of which is to foster students' ability to develop and maintain healthy romantic relationships in adulthood. However, while an education aimed at developing this capacity in young people is welcomed, the RSE guidance does not directly address conceptions of romantic love that shape how we actually conduct our love lives. Romantic love myths are a fundamental part of cultures across the world and greatly influence our behaviour and decision‐making in romantic relationships. Belief in these myths is associated with negative relationship outcomes. Therefore, if we wish to improve students' capacity to effectively negotiate future relationships, RSE must directly address conceptions of romantic love and its associated myths. This paper proposes five criteria against which to assess student beliefs to determine appropriate educational responses to them. Given love's complex nature, and the manner in which related beliefs are held, it is argued that addressing this topic through open philosophical exploration would be a prudent educational approach to adopt within the classroom. This may temper some of the potential harms of love myths while respecting the right of students to freely hold and pursue their own conceptions of love.